A Conversation on Literacy: Thinking Outside the Margins (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
How are teachers better engaging students in literacy? Disengagement in classrooms is one of the greatest struggles faced across educational institutions. In the English Language Arts (ELA) field, educators are taking immense strides to adapt their instruction to promote all forms of literacy, including visual and media literacy. Through this, students become aware of all the literacy around them. Creating literacy engagement for students in the ELA classroom has been an ongoing discuss for educators. This discussion has fueled several conversations from past to present teachers coming together with the willingness to adapt instruction and fuse the two worlds of the student: inside and outside the classroom. Educators must remind students that literacy moves beyond the classroom.